Fluorescent carbon dots from Indian Bael patra as effective sensing tool to detect perilous food colorant. (30th March 2022) - Vijeata, Anjali; Chaudhary, Savita; Chaudhary, Ganga Ram
Highlights: Novel approach to fabricate carbon dots from different parts of Bael patra fruit for fluorometric detection of Allura red. Morphological and chemical composition checked using sophisticated techniques. Developed particles material act as an excellent co-absorbent for Allura red and Fe 2+ ion. Sensor worked well in presence of amino acids and in different water and food samples. Abstract: Herein a simple strategy has been demonstrated for the synthesis of environmentally amiable and highly fluorescent carbon dots from the most useful plant of Indian classical Ayurveda i.e. Bael patra fruit. The morphological features and chemical composition of the prepared carbon dots were characterized through High resolution transmission electron microscopy, Field emission scanning electron microscopy and X-ray photoelectron spectroscopy. Owing to their highly emission nature, the applicability of carbon dots was tested against various food colorant i.e. Allura red. Under the optimized conditions, the decreased fluorescence intensity exhibited a good linear relationship with increasing concentration of Allura red. Additionally, an extensive research was carried out to determine the adsorption efficiency of carbon dots for Allura red and heavy metals. Based on the context, here we report the novelty of this work, demonstrating the decontamination of various samples from Allura red and heavy metals with the application of carbon dots.